2006
DOI: 10.1124/mol.105.015644
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-Dependent Desensitization by Anandamide of Vanilloid Receptor-1 (TRPV1) Function in Rat Skeletal Muscle Arterioles and in Chinese Hamster Ovary Cells Expressing TRPV1

Abstract: It has been proposed that activation of vanilloid receptor-1 (TRPV1) affects the vasotone of resistance arteries. One of the endogenous activators of TRPV1 is anandamide. The effects of anandamide on TRPV1 responsiveness were tested on isolated, pressurized (80 mm Hg) skeletal muscle (m. gracilis) arterioles (179 Ϯ 33 m in diameter). We found that the TRPV1 agonist capsaicin (1 M) elicited a substantial constriction in isolated arterioles (51 Ϯ 12%). In contrast, anandamide (0 -100 M) did not affect arteriolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 40 publications
5
73
0
Order By: Relevance
“…Anandamide is the most abundant endogenous endocannabinoid and regulates systemic energy metabolism [43]. Anandamide in skeletal muscles participates in the regulation of TRPV1 function [44,45]. We showed that anandamide treatment significantly increased TRPV1 expression (Supplementary information, Figure S6).…”
Section: Discussionmentioning
confidence: 80%
“…Anandamide is the most abundant endogenous endocannabinoid and regulates systemic energy metabolism [43]. Anandamide in skeletal muscles participates in the regulation of TRPV1 function [44,45]. We showed that anandamide treatment significantly increased TRPV1 expression (Supplementary information, Figure S6).…”
Section: Discussionmentioning
confidence: 80%
“…Vasoconstriction in response to TRPV1 stimulation was reported decades ago (Molnar and Gyorgy, 1967;Toda et al, 1972;Donnerer and Lembeck, 1982;Duckles, 1986;Edvinsson et al, 1990) and this effect was confirmed later (Szolcsanyi et al, 2001;Dux et al, 2003;Scotland et al, 2004;Keeble and Brain, 2006;Lizanecz et al, 2006). Nonetheless, these responses were not thought to be of interest.…”
Section: Discussionmentioning
confidence: 88%
“…We have recently shown that stimulation of TRPV1 in skeletal muscle arterioles results in a substantial vasoconstriction (Lizanecz et al, 2006). Moreover, intra-arterial injection of capsaicin into the hind limb evoked a dose-dependent increase in blood flow in the skin (probably representing vasodilatation in this organ) and simultaneously, a decrease of blood flow in skeletal muscle (representing vasoconstriction) (Kark et al, 2008).…”
Section: Pharmacology Of Trpv1 In Peripheral Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPV1 ion channels have important functions as cellular sensors, and are involved in nociception, taste perception, thermosensation, mechano‐ and osmolarity sensing, and regulation of signal transmission 15, 55, 56. In addition to ECS and physicochemical activators,15, 33, 55, 56, 57, 58 TRPV1 is activated by tetrahydrocannabinol, cannabinol, cannabigerol and some propyl homologs of THC and cannabigerol 59, 60, 61, 62, 63, 64, 65, 66, 67. Cannabichromene (CBC), cannabidiol, and cannabinol are strong TRPA1 agonists and desensitizers, and THCV (from a botanical extract) is a potent regulator of TRPA1 62…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%